Lateral Congenital Sinus of the Upper Lip - Raibagkar, Santosh; Vyas, U. H. (Indian Journal of Plastic Surgery, 1986)
A case of congenital lateral lip sinus has been presented because of its rarity. Literature and aetiology have been briefly reviewed.